MANFAAT PEMBERIAN MANUAL TERAPI DAN CODMAN PENDULAR EXERCISE TERHADAP AKTIVITAS FUNGSIONAL PASIEN FROZEN SHOULDER - Isidorus Jehaman; Sabirin Berampu; Redi Tantangan; Timbul Siahaan; Simson Sinuhaji (JURNAL PENGMAS KESTRA (JPK), 2021)
Background: Frozen shoulder is a joint disorder that causes limited motion of the shoulder joint in all directions of movement, causing both physical and functional problems. This activity aims to see the benefits of manual therapy and pendular codman exercises in increasing the activity of frozen patients at Grandmed Lubuk Pakam Hospital in 2019. Manual therapy methods and codman pendular exercises were given to 24 patients at the Physiotherapy Clinic of Grandmed Lubuk Pakam Hospital. The measuring instrument used to measure the functional activity ability of the shoulder is the index of shoulder pain and disability with the 0% -60% category being improving and 61% -100% being worse. Based on the results obtained during manual therapy and codman pendular exercise, it shows that the ability of the patient's shoulder functional activity has increased. where manual therapy and pendular codman exercise from 16 samples, the ability of shoulder functional activity with a SPADI value of 100% decreased and after manual therapy and pendular codman exercises for 3 times decreased to 12.5% ​​decreased and 87.5% improved. Based on these data it can be neglected that there is an effect of offering manual therapy exercises and pendular codman in increasing the patient's shoulder functional activity by 87.5%